Producing Hip Implants Of Titanium Alloys By Additive Manufacturing - Evgenii, Borisov (2016)
Additive manufacturing (AM) technologies and in particular Selective Laser Melting (SLM) allow making complex-shaped individual implants of titanium alloys with high biocompatibility, mechanical properties and improved osseointergration by surface texturing. In this work the possibility of producing a custom-made hip implant from Ti-6Al-4V powder according to the data acquired by computer tomography of the patient is shown. Different heat treatments were applied in order to achieve the better combination of tensile strength and elongation by partial decomposition of martensitic phase. The implant has been installed to the patient, the postoperative supervision has shown a good result, the patient can move with the installed implant. Applying AM for producing the custom hip implant allowed to decrease the operation time and lessen the risk of the infection ingress.